Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada PKBM Bhakti Sejahtera - Aris Aris; Ryan Anggara; Zaimi Akhmad Zamzami (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
Bhakti Sejahtera Tangerang is a school located in the district of Tangerang which have the aim ofhelping the government program in the field of non-formal education and produce qualified younggeneration, these schools also strive to provide a good service for this school masarakat.Namun alsohas disadvantages mainly the new admissions system that exists. New admissions system that existedat this school has been using a computer but still using a simple application, so often there is a delayin the presentation of information, so there needs to be a new system that can improve the existingsystem. To resolve this problem, the school needs to use the new system with a computerized systemthat has a better database to store its data. With a computerized system that better data processingwill be more efficient and to minimize errors in the data pengimputan. Thus the new admissionssystem that there will be better and can improve service to masarakat who want to registerKeywords :Mutimedia, Computer Generated Imagery, Software, Computer, Technology.